Blog educacional e dispositivos móveis: uma proposta de intervenção em cursos técnicos integrados ao ensino médio na modalidade de educação de jovens e adultos - LIMA, Mariceia Ribeiro (2019)
In the last five decades we have seen moments of deep and rapid changes that have reshaped the material base of society. Among the technological innovations that have emerged, mobile communication devices (cell phones and smartphones) have become more popular and have become so indispensable objects in the daily life of each one that, today, many are unable to live without being connected to these devices. The present research aims to analyze the possibilities of using digital technologies in the classroom through a methodological proposal with Educational Blog and mobile devices. The research is based on the works of Bottentuit Junior (2017; 2018) Shin, Kang (2015); Moura (2017) and in the researches that use the Blog as a learning tool (SOUSA, 2013, BOTTENTUIT JUNIOR, 2007, SILVA, 2013, ARAÚJO, 2015, VASCONCELOS, 2016). It is a Pedagogical Intervention research carried out in the Technical Course in Computer Networks, Youth and Adult Education modality, of the IFMA Campus São José de Ribamar, with a sample of 12 students. The instruments used in the research were: observation sheet and questionnaire. The research product is a Good Practices Handbook for use of Educational Blog with the help of mobile devices, built during the development of the research. The results allow us to conclude that the use of Mobile Allied Blogs in EJA classes is an appropriate strategy for this audience, with enriching benefits, as they stimulate collaborative writing and broaden students' perceptions about cellular devices as tools that can favor the construction of knowledge of any nature.